Evaluation of the U.K. DFID-Financed Technical Assistance GDDS Project for Selected Anglophone African Countries (2001-06). (Policy Papers; Policy Paper ;, 2008)
This review of Phase I of the technical assistance (TA) General Data Dissemination System (GDDS) project (2001-2006) for 15 Anglophone African countries1-funded by the U.K. Department for International Development (DFID) and executed jointly by the Fund and the World Bank-(henceforth, referred to as the Anglophone African (AAf) project) focuses mostly on the components that were implemented by the Fund's Statistics Department (STA). The review draws on various internal and periodic evaluations of project execution and reports by technical assistance providers. The GDDS-part of the Fund's Data Standards Initiative-defined the framework for the AAf project. The main goal of the project was initially limited to assisting countries to become participants in the GDDS via preparatory workshops and development of metadata and plans for improvement. The goal was subsequently expanded to providing TA and promoting greater awareness and regional cooperation.